Pemberian Edukasi Mengenai Ragam Makanan Sehat Siswa SMP Negeri 8 Semarang - Hidayat, Umar; Rahmawati, Fiqhi Cahyaningrum; Agina, Grace; Chaerunnisa, Zahra Rizqika (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Ivet, 2022)
Adolescence is the stage at which age begins to be physically active compared to previous periods. Many factors affect the nutritional status of this group, both directly and indirectly. The food factor consumed is a direct determinant of nutritional status in addition to a history of illness or disease. At this age, the level of knowledge of a variety of healthy snacks and adequate nutritional content is still low, so it is necessary to provide education to this age group. SMP Negeri 8 Semarang was chosen as a place of service because the school was adjacent to an area that sells various kinds of food and becomes a gathering place for students after school. Various high-calorie, high-sugar, and low-fiber snacks are sold there. Education was provided online using the Zoom Meeting due to the COVID-19 pandemic situation. The educational activities was successful and conducive. The achievement of the target and the output of this activity has been achieved, namely the feedback from the participants and the question and answer session went well. This shows that there was a change in the level of adolescent knowledge of the material provided. Providing education about this material should be done regularly in schools. This is in view of the importance of knowledge about types of nutritious food and the fulfillment of a balanced nutritional diet, as well as its impact on adolescent growth and development, degenerative diseases, and the menstrual cycle at a young age, so that future health can always be maintained.